Heart failure with mildly reduced ejection fraction: not a mid-range prognosis. (3rd October 2022) - Borges-Rosa, J; Almeida, J P L; Martinho, S; Marques-Alves, P; Oliveira-Santos, M; Goncalves, L
Abstract: Introduction: Heart failure with mildly reduced ejection fraction (HFmrEF) has been recognized in the last heart failure guidelines of the European Society of Cardiology, replacing the concept of "midrange ejection fraction". There is limited data regarding mortality outcomes of HFmrEF compared to heart failure with reduced (HFrEF) and preserved (HFpEF) ejection fraction. Purpose: We aimed to evaluate whether HFmrEF has a different prognosis after an acute heart failure (AHF) episode, in a real-world contemporaneous southern European population. Methods: We retrospectively studied 1026 patients admitted to our emergency department between November 2016 and December 2017 with discharge diagnosis of AHF. Median follow up was 5 months (IQR 3–11 months). Incidence of rehospitalization, cardiovascular (CV) and all-cause mortality were evaluated through multivariable logistic regression models and by Kaplan-Meyer survival curves. Results: From all patients, 782 were categorized in HFrEF (34.1%), HFmrEF (19.4%) and HFpEF (46.4%). There was heterogeneity between groups. Compared to HFrEF, HFmrEF patients were older (80 [74–84] vs. 76 [67–82] years, p<0.001), with lower prevalence of males (61.2% vs. 76.4%, p=0.004) and coronary artery disease (CAD) (35.5% vs. 47.6%, p=0.024), but higher rates of valvular heart disease (VHD) (48.0% vs. 29.6%, p<0.001). Compared to HFpEF, HFmrEF subjects had higher prevalence of males (61.2% vs. 40.8%, p<0.001) and CAD (35.5% vs. 13.2%, p<0.001). At admission, patients with HFmrEF and HFrEF had similar serum creatinine e B-type natriuretic peptide values, but higher than the HFpEF group: 1.38±0.7 vs. 1.45±0.7 vs. 1.28±0.8mg/dL, p=0.019 and 701 [385–1191] vs. 1000 [494–1776] vs. 360 [214–717]pg/mL, p<0.001, respectively. HFmrEF patients had higher rates of hospitalization (71.7% vs. 43.8%, p<0.001), follow-up readmissions (27.6% vs. 18.7%, p=0.034), CV (11.8% vs. 5.0%, p=0.025) and all-cause mortality (25.7% vs. 14.9%, p=0.015), compared to HFpEF; no differences comparatively to HFrEF. There was no difference between groups regarding the length of hospitalization (9 [5–15] vs. 8 [5–15] vs. 10 [6–17] days, p=0.302). In multivariate logistic regression model adjusted for age, sex, SBP, CAD, VHD, creatinine, and BNP, HFmrEF increased the risk of CV (OR 2.9, 95% CI 1.2–6.7, p=0.016) and all-cause mortality (OR 2.1, 95% CI 1.2–3.9, p=0.011), but not follow-up readmissions (OR 1.7, 95% CI 0.9–2.9, p=0.059). Kaplan-Meier estimates of CV, and all-cause mortality are shown in Figure 1. Conclusions: HFmrEF have a similar prognosis to HFrEF and worse than HFpEF, with more readmissions, CV and all-cause mortality, after an AHF episode. Funding Acknowledgement: Type of funding sources: None.